Dr. Johnson's Printer : The Life of William Strahan - Cochrane, J.A., (European History and Culture - Book Archive pre-2000., 1964)
Strahan was King's Printer and the owner of the greatest printing house in London during the 18th century. A.o.: David Hume, David Hall and America, The Franklins, Johnson.